2023
DOI: 10.1109/tmm.2022.3203211
|View full text |Cite
|
Sign up to set email alerts
|

RV-TMO: Large-Scale Dataset for Subjective Quality Assessment of Tone Mapped Images

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Indeed, participants are fully informed that they are being recruited for a research study. Consequently, this platform allows researchers to eliminate ethical concerns, and it further improves the reliability of collected data [22].…”
Section: Crowdsourcing Experimentsmentioning
confidence: 99%
“…Indeed, participants are fully informed that they are being recruited for a research study. Consequently, this platform allows researchers to eliminate ethical concerns, and it further improves the reliability of collected data [22].…”
Section: Crowdsourcing Experimentsmentioning
confidence: 99%
“…Observer screening is essential steps of collecting a reliable Quality of Experience (QoE) database. A range of methods [1,2,3,4,5] with varying complexities have been proposed, and various standards [6,7,8] include recommendations for this purpose. It has also been demonstrated that training learning-based metrics on recovered MOS can enhance their performance to a certain extent [9].…”
Section: Introductionmentioning
confidence: 99%